Estrategias de afrontamiento para mejorar el manejo de las emociones causado por el confinamiento social en diez niños del barrio 25 de diciembre de la ciudad de Loja, período 2020 – 2021. - Banegas Loja, Vanessa Alexandra (2021)
The general objective of the research work entitled COOPING STRATEGIES TO IMPROVE THE MANAGEMENT OF EMOTIONS CAUSED BY SOCIAL CONFINEMENT IN TEN CHILDREN FROM THE NEIGHBORHOOD 25 DE DICIEMBRE OF THE CITY OF LOJA, PERIOD 2020 - 2021, was to propose coping strategies to improve the management of emotions caused by social confinement in ten children from the neighborhood 25 de December of the city of Loja. A quantitative methodology was applied; of descriptive type; non-experimental design and transversal cut, in addition, the scientific, inductive, deductive, statistical, analysis and synthesis methods were used, which contributed favorably to the theoretical foundation; as a technique the survey on coping strategies was used, in addition, Fredrickson's Scale of positive and negative emotions was used as an instrument to a sample of ten children; from the most relevant results it was evidenced that, the main emotions found are: the positive emotion of love, which has been experienced in 70% with high frequency, however, in 40% it is witnessed with low intensity; the negative emotion of sadness, is experienced in 40% often with medium intensity; from these results it is concluded the emotion of love is experienced with high frequency and low intensity, and the emotion of sadness is experienced in medium frequency and intensity; facing these results it is proposed Coping strategies to improve the management of emotions caused by social confinement and it is recommended to the neighborhood to apply the intervention proposal.